The Early Eocene Decapod Crustacean Fauna of the Lookingglass Formation, Oregon (Bulletin of the Museum of Natural History, University of Oregon, 2022)
The Tenmile Member of the Lookingglass Formation (Lower Eocene) of southwest Oregon produces a diverse marine invertebrate fossil fauna including at least eleven genera of decapod crustaceans. This is the earliest Cenozoic crab fauna known from the Pacific Northwest, and is one of the earliest on the west coast of North America. The fossiliferous sediments are generally fine-grained mudstones without much compaction, with evidence suggesting a low-energy environment in relatively shallow water and a mild warm climate. The abundance of complete crabs at some localities is exceptional, and suggests repeated mass mortality caused by environmental conditions. Modern relatives of several of the taxa are burrowers. The fossils are often well-preserved in concretions. Preservation in concretions preferentially involves decaying crab corpses; other taxonomic groups are underrepresented in concretions. The fauna includes an unusual number of raninid crabs, in three genera (Raninoides vaderensis, Rogueus orri, and Doraranina manleyi) of which the latter two genera are only known from this formation. A scyllarid, Llajassus caesius, is one of a very few of this group known as fossils. Dominant in numbers is the euryplacid crab Orbitoplax weaveri, with specimens numbering in the thousands. Other crustaceans include the ghost shrimp Ctenocheles hokoensis, Panopeus baldwini (the largest crab in the fauna), Eriosachila orri, Palaeopinnixa rathbunae, and rare examples of Archaeozius occidentalis and Marycarcinus hannae. The abundance of specimens allows examination of several taxa as populations rather than individuals as is frequently the case in fossil crabs.